MELAWAN PENGANGURAN: PEMIKIRAN EKONOMI AL-SHAYBANI - HIKAM, MUHAMMAD (Islamic Economics and Business Faculty of UIN Antasari, 2015)
Abstract: This paper seeks to show that government policies that restrict intervention or no intervention at all in the unemployment rate become a-historical view and even irrational. The Postulat is in historical data that occurs at the time of al-Amin and al-Ma'mun and